(untitled) (New Yor, NY., 2006)
Water-quality trading is a market-based approach that allows a facility to meet its regulatory obligations by using the pollutant reductions created by another facility capable of doing it at a much lower cost. This resource is a practical guide for wastewater treatment plants to use in evaluating the potential for water-quality trading and provides the framework for designing and implementing the trade.
Keywords: Water quality management,Water,Watershed management; Pollution,Government policy,Government policy; United States,United States,United States